Gamification on English vocabulary learning through technology among middle basic education students at a public institution of Loja city. School year 2022-2023. Gamificación en el aprendizaje del vocabulario Inglés a través de la tecnología en estudiantes de educación básica media de una institución pública de la ciudad de Loja. Año lectivo 2022-2023. - Ramirez Saraguro, Evelin Paola (2023)
This research encompasses gamification through technology as an educational strategy that makes use of game elements contributing and facilitating the acquisition of new vocabulary in an entertaining and objective way. Therefore, the purpose of this research was: to increase English vocabulary learning by using gamification through technology. In addition, the mixed method was employed since both the qualitative and quantitative parts of the study were covered. Likewise, the research design corresponds to a research cycle. As for the instruments, the pretest, posttest, observation guide and checklist were applied to record the data obtained and observed during the development of the research. In addition, the data analysis was covered whit the descriptive statistics, it was represented in tables and graphs and also the thematic analysis to interpret the observations noted in the instruments. As results, it was established that the application of gamification is effective in the learning of the use of pronouns and prepositions, likewise in the meaning of nouns, verbs and adjectives of the English vocabulary, as well as that the Wordwall, Kahoot and Baamboozle games are useful means to work on learning new words and also that technology is a tool that facilitates the presentation of the games, assimilation and retention of the theory. To conclude, it is recommended to incorporate gamification to improve vocabulary learning, to implement the tools mentioned above because they engage and motivate students to participate in learning and finally to include the technology together with games because it facilitates the work and learning outcomes. Keywords: vocabulary learning, benefits of gamification, gamified teaching strategies, use and meaning of vocabulary.